KETIDAKADILAN GENDER TERHADAP TOKOH HANUN DALAM NOVEL DIA YANG HARAM KARYA ISRINA SUMIA - Enjella Marahmi; Samsiarni; Rici Gemarni Tatalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of gender injustice experienced by women in social and family life. This phenomenon is clearly depicted in the novel Dia yang Haram by Isrina Sumia through the main character Ismi Hanun Nazma. This novel is interesting to study because it clearly displays five forms of gender injustice according to Mansour Fakih, namely marginalization, subordination, stereotypes, violence, and double workload. The purpose of this study is to describe the forms of gender injustice experienced by the character Hanun in the novel Dia yang Haram by Isrina Sumia. This type of research is qualitative research with descriptive methods. The research instrument is the researcher herself with the help of a data inventory format. The research data are in the form of quotes, dialogues, and narratives in the novel that reflect gender injustice towards the character Hanun. Data collection techniques are carried out through reading, recording, classification, and content analysis. The data analysis technique uses a hermeneutic approach, namely interpretation of the text. Data validity is obtained through triangulation of theory and investigators. The results of the study show that the character Hanun experiences various forms of gender injustice. First, marginalization in the form of social exclusion, restrictions on educational rights, and neglect of family affection. Second, subordination is evident in Hanun's placement in a position perceived as inferior to her siblings. Third, stereotypes are demonstrated through negative labels such as illegitimacy and the assumption that she is unworthy of achievement. Fourth, violence occurs in physical, verbal, psychological, and emotional forms from family and the community. Fifth, Hanun experiences a double workload when she has to manage domestic chores and work outside the home without proper compensation. Keywords: Gender Injustice, She Who Is Forbidden, Isrina Sumia